Plasma Phosphatidylethanolamine and Triacylglycerol Fatty Acid Concentrations are Altered in Major Depressive Disorder Patients with Seasonal Pattern. Issue 6 (24th April 2017) - Otoki, Yurika; Hennebelle, Marie; Levitt, Anthony J.; Nakagawa, Kiyotaka; Swardfager, Walter; Taha, Ameer Y.
Abstract: Disturbances in peripheral and brain lipid metabolism, including the omega‐3 fatty acid docosahexaenoic acid (DHA), have been reported in major depressive disorder (MDD). However, these changes have yet to be confirmed in MDD with seasonal pattern (MDD‐s), a subtype of recurrent MDD. The present exploratory study quantified plasma plasmalogen and diacyl‐phospholipid species, and fatty acids within total phospholipids, cholesteryl esters, triacylglycerols and free fatty acids in non‐medicated MDD‐s participants ( n = 9) during euthymia in summer or fall, and during depression in winter in order to screen for potential high sensitivity lipid biomarkers. Triacylglycerol alpha‐linolenic acid concentration was significantly decreased, and myristoleic acid concentration was significantly increased, during winter depression compared to summer‐fall euthymia. 1‐stearyl‐2‐docosahexaenoyl‐ sn ‐glycero‐3‐phosphoethanolamine, a diacyl‐phospholipid containing stearic acid and DHA, was significantly decreased in winter depression. Concentrations of cholesteryl ester oleic acid and several polyunsaturated fatty acids between summer/fall and winter increased in proportion to the increase in depressive symptoms. The observed changes in lipid metabolic pathways in winter‐type MDD‐s offer new promise for lipid biomarker development.